Lithospheric structure of an incipient rift basin: Results from receiver function analysis of Bransfield Strait, NW Antarctic Peninsula - Biryol, C. Berk; Lee, Stephen J.; Lees, Jonathan M.; Shore, Michael J. (Polar Science, 2018)
Bransfield Basin (BB), located northwest of the Antarctic Peninsula (AP) and southeast of the South Shetland Islands (SSI), is the most active section of the Antarctic continental margin. The region has long been (50 Ma) a convergent plate boundary where the Phoenix plate was subducting beneath the Antarctic Plate and is characterized by long-lived arc magmatism and accretion. However, the collision of the Antarctic-Phoenix spreading center with the subduction front near SSI (ca. 4 Ma) gave way to the opening of slab windows and dramatic decrease in the subduction rate of the Phoenix plate beneath AP and SSI. Consequently, the Phoenix slab began to rollback slowly along the South Shetland Trench (SST), giving way to slow extension in the back-arc region and rifting along the BB. Although there is consensus on the factors that control the current deformation and extension of the BB, the origin of the BB and the tectonic configuration of the basin are still unclear. Most of the controversy stems from uncertainties regarding the crustal thickness of the BB. Hence, we computed teleseismic receiver functions for 10 broadband stations in the region that belong to existing permanent and temporary deployments in order obtain robust constraints on the lithospheric structure and crustal thickness of the BB, as well as the AP and SSI. Our results indicate that the crust is thinning from 30 km to 26 km from the AP towards the South Shetland trench and Central BB showing the asymmetrical character of the rift basin. The crustal thickness and Vp/Vs variations are less pronounced along the AP but very significant across the SSB indicating the lithospheric scale segmentation of the South Shetland Block (SSB) and the incipient rift basin under the control of the opening of slab window and the roll-back of stalled Phoenix slab. High Vp/Vs ratios (∼1.9) beneath BB and SSI, agree well with the nascent rift character of BB, the presence of a steep Phoenix slab and consequently a wider mantle wedge characterized by the presence of ...